Teologi Proses Mengenai Allah dan Problem Kejahatan: Suatu Tinjauan atas Kasus Al-Nakba - Anodya Ariawan Soesilo (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2017)
Abstract This article presents process theology which is seen as an alternative modus offered by particular group of Christianity in dealing with radical evil. Process theology is a philosophical theology. It passes through the principles of concrescence and prehension offering the idea to identify that God's works are more likely imanent persuasion, namely, the action of love and suavity. Concrescence is acknowledgement that the actual entities not denying if its existence was formed by past objective data (experience), but deliberately work onto prehension that grasp goodness for transforming and rehabilitating the sensitivity of human history. This article will expose the space for acting faith in the mode of human responsibility, keeping an open dialogue as well restraining the false arogancy of identity fanatism of quasi-religious, persisting, and defending humanity. Such concept is based on the hope of the God who is perceptive and saving as a contribution to solve the problem of the complexity of Al-Nakba. In the mechanism of thinking process, the shadow of the failure does not disappear so that humans are asked to be seriously responsible for this. The idea of process has described God as the God who involves in relationships with humans, refuting the monarch description of the God who demands and punishes. God in theology process is a figure who does not exercise power excessively. The God who guides, accompanies, and participates patiently in the world's events still appreciates the independency of humans. That does not mean a justifi cation of irresponsible freedom. The true freedom is aligned with the God's design, namely, the righteousness, sublimity, and kindness.   Abstrak Artikel ini menghadirkan pemikiran teologi proses, yang dilihat, sebagai modus alternatif kekristenan tertentu dalam menghadapi bengal kejahatan radikal. Teologi proses adalah teologi filosofis. Teologi proses melalui prinsip konseptual konkresi, prehensi, menawarkan gagasan untuk mengenali bahwa karya Tuhan lebih mengarah kepada himbauan imanensi, yaitu tindakan cinta dan rahmat kelembutan. Konkresi sebagai pengakuan adalah bahwa entitas aktual tidak memungkiri dirinya turut dibentuk oleh data objektif (pengalaman) masa silam, namun mengusahakan kepada prehensi yakni kesengajaan untuk mencengkeram kebaikan, demi perubahan dan perbaikan sejarah manusia yang sensitif. Hasil penelusuran artikel ini mengintrodusir ketersembunyian Allah akan mengekspos ruang bagi iman yang bertindak dalam tanggung jawab manusia. Untuk terus melakukan dialog terbuka, yang mengempangkan kemangkakan semu fanatisme identitas dari kuasi religius, seraya gigih mempertahankan martabat manusia. Mendasarkan harapan kepada Allah yang tanggap dan menyelamatkan sebagai kontribusiÂ memulihkan problem Al-Nakba yang muskil. Dalam pemikiran proses, bayang-bayang kegagalan tidak sirna, sehingga menuntut tanggung jawab serius manusia. Terobosan gagasan proses menggambarkan Allah sebagai pribadi yang melibati relasi dengan manusia daripada menyodorkan gambaran Tuhan monarkis yang banyak menuntut dan menghakimi. Gambaran Allah dalam pemikiran teologi proses adalah Pribadi yang dapat menahan diri dari penggunaan kekuasaan eksesif. Allah yang dengan sabar membimbing, menyertai, berpartisipasi dalam menjejaki perisiwa dunia, dan masih menghargai kemandirian individu, kendati bukan kebebasan mana suka, melainkan yang selaras dengan kehendak Allah yang luhur, yakni mengejar visi kebenaran, keindahan, dan kebaikan.